The Evolution of the Concept of “Farhang” in Persian Dictionaries and Lexicographers’ Criticisms of each other’s Method from the Compilation of Fors to Bahar-e Ajam - Saeed khosropour; Abdollah Radmard (تاریخ ادبیات)
This study introduced Persian dictionaries and prominent lexicographers and explored the evolution of the concept of “farhang” and lexicographers’ criticism of each other in Persian-Persian dictionaries. It examined chronologically twenty-three dictionaries from Fors to Bahar-e Ajam and clarified some of the reasons why the words “farhang” (literally meaning culture, but here meaning dictionary) and “loghat” (meaning vocabulary) – juxtaposedly meaning dictionary – have been applied. Exploring the changes of the word “farhang” showed this trajectory of change: a) not dedicating an entry for the word “farhang” (meaning dictionary), b) including one entry for “farhang” including its various meanings like “dictionary”, and c) dedicating one entry for each meaning of the word. Criticisms have also shifted in Persian-Persian dictionaries from structure to content (i.e., from form to meaning). Exploring the works of the lexicographers in the studied period, including criticisms of twelve lexicographers on the works of each other, showed that they have dealt at first with ordering words, ordering entries and chapters, and the quality and number of poetry examples, and then have dealt with the correctness and falseness of words, and finally the correctness of meaning. That is, they have gone from focusing on general issues to details. The most prominent critic and lexicographer is Lala Tek Chand Bahar, the compiler of Bahar-e Ajam. He adopted methods like “including his own criticizing ideas”, “mentioning others’ criticizing ideas without mentioning his own judgement”, and “mentioning others’ criticizing ideas and simultaneously including his own critical ideas”. Dealing more than anyone with criticism, he shows that his works are in line with other criticism methods of India in the 12th century AH.